+0

# How to do this calculation?

0
78
1

How to do (25/4*sqrt(3)/(5+2.5sqrt(3)) this step by step?

Guest Sep 20, 2017
edited by Guest  Sep 20, 2017
Sort:

#1
+79671
+1

I'm assuming that you have

(5+2.5sqrt(3))/(25/4*sqrt(3) )   =

5 / (25/4*sqrt(3) )    +  2.5sqrt (3) / (25/4 * sqrt (3) )  =

5 / (6.25 sqrt (3) )   +  2.5sqrt (3) / ( 6.25 * sqrt (3) )   =

5 / (6.25 sqrt (3) )   +  2.5 / ( 6.25  )

.8 / sqrt (3)   +  .4      =        rationalize the denominator in the frist fraction

.8sqrt (3) / [ sqrt (3) * sqrt (3) ]  +   .4  =

.8 sqrt (3) / 3  +   .4   =              get a common denominator

[.8sqrt (3)  + .4 (3)]  / 3  =

[ .8 sqrt (3)  + 1.2 ]  / 3  =

.4 [ 2sqrt (3)  + 3 ]  / 3  =

(.4/3) [ 2sqrt (3)  + 3 ]  =

(4/30) [ 2sqrt (3) + 3 ] =

(2/15) [ 2sqrt (3) + 3  ]  ≈  .861880

CPhill  Sep 20, 2017

### 22 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details